Silencing of Iron and Heme-Related Genes Revealed a Paramount Role of Iron in the Physiology of the Hematophagous Vector Rhodnius prolixus - Walter-Nuno, Ana B.; Taracena, Mabel L.; Mesquita, Rafael D.; Oliveira, Pedro L.; Paiva-Silva, Gabriela O. (Frontiers in Genetics, 2018)
Iron is an essential element for most organisms However, free iron and heme, its complex with protoporphyrin IX, can be extremely cytotoxic, due to the production of reactive oxygen species, eventually leading to oxidative stress. Thus, eukaryotic cells control iron availability by regulating its transport, storage and excretion as well as the biosynthesis and degradation of heme. In the genome of Rhodnius prolixus, the vector of Chagas disease, we identified 36 genes related to iron and heme metabolism We performed a comprehensive analysis of these genes, including identification of homologous genes described in other insect genomes. We observed that blood-meal modulates the expression of ferritin, Iron Responsive protein (IRP), Heme Oxygenase (HO) and the heme exporter Feline Leukemia Virus C Receptor (FLVCR), components of major pathways involved in the regulation of iron and heme metabolism, particularly in the posterior midgut, where an intense release of free heme occurs during the course of digestion. Knockdown of these genes impacted the survival of nymphs and adults, as well as molting, oogenesis and embryogenesis at different rates and time-courses. The silencing of FLVCR caused the highest levels of mortality in nymphs and adults and reduced nymph molting. The oogenesis was mildly affected by the diminished expression of all of the genes whereas embryogenesis was dramatically impaired by the knockdown of ferritin expression. Furthermore, an intense production of ROS in the midgut of blood-fed insects occurs when the expression of ferritin, but not HO, was inhibited. In this manner, the degradation of dietary heme inside the enterocytes may represent an oxidative challenge that is counteracted by ferritins, conferring to this protein a major antioxidant role. Taken together these results demonstrate that the regulation of iron and heme metabolism is of paramount importance for Rhodnius prolixus physiology and imbalances in the levels of these key proteins after a blood- meal can be extremely deleterious to the insects in their various stages of development.